Проблеми використання пристроїв на фотонно-кристалічних волокнах для забезпечення перешкодозахищеності систем передачі - Филипенко, О. І.; Сичова, О. В. (Харьковский национальный университет радиоэлектроники, 2015)
In this paper the connection problem photonic-crystal fiber with a standard fiber was researched. Photonic-crystal fiber used as dispersion compensators in optical transmission systems, thus increasing the noise immunity.
Keywords: фотонно-кристалічне волокно; хроматична дисперсія; з'єднання оптичних волокон